Analysis of an ethnomathematics-based problem-solving test instrument in the Maggale-Majjekka Game and the Syekh Yusuf Grand Mosque of Gowa - Nur Qadriana Ramadani Iqbal; Siti Sabrina; Fitriani Nur; Sitti Mania; Lisnasari Andi Mattoliang (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to develop and assess the quality of an ethnomathematics-based mathematical problem-solving test instrument adapted from the traditional Maggale-Majjekka game and the architecture of the Syekh Yusuf Gowa Grand Mosque. This study used a quantitative descriptive method involving 17 ninth-grade students as subjects. The instrument consisted of 10 descriptive questions at cognitive levels C4-C6 and was assessed using Polya’s four-step rubric. The analysis of the instrument’s quality included item validity, reliability, difficulty level, and discriminating power. The results showed that nine items were valid, while one item was invalid. The Cronbach’s Alpha reliability value of 0.831 indicates excellent internal consistency. The difficulty level analysis shows that one item is classified as easy, two items are moderate, and seven items are difficult. The discriminating power shows that seven items are in the fair category, while three items are in the poor category. These findings indicate that the instrument is suitable for measuring problem-solving skills in a local cultural context and contributes to the development of standardised ethnomathematics-based assessments. Further research could expand the trial to a larger sample and refine items with low discriminating power. The study concludes that the developed ethnomathematics-based problem-solving test instrument demonstrates satisfactory psychometric properties and is appropriate for assessing students’ higher-order mathematical thinking within a cultural context. This research contributes by providing an initial model for integrating local cultural elements into standardized mathematical assessment, as well as offering empirical evidence that ethnomathematics-based instruments can achieve both contextual relevance and measurement validity.